THE BAFFLE V AND ERECT INFLUENCE ON THE DISTILATION SIEVE PLATE TOWARD MIXING SYSTEM AIR-WATER - dewati, Retno (Jurnal Teknik Kimia, 2010)
The baffle influence to the degree of liquid mixing in the plate and the pressure drop on the plate has beenstudied in this research. The operational pressure in this research is limited in the atmospheric pressure .Thedistillation column that used in the research has 0.2m diameter and 1.4 m height with the distance betweentrays is 0.4 m. The research was carried out by to flows water into the column with the flow rate of water are105 l/h, 149 l/h, 189 l/h and to flows air into the lower of the column with superficial speed from 0 to 0.3 m/s.After steady state is required the dry plate pressure and the pressure drop because the difference between theheight of clear liquid and the height of foam is measured. The mixing degree is determined by stimulusresponse method, i.e flows air into the system, then give a tracer (i.e. NaCl saturated 20 CC) as a stimulatorthat injected into the fuild to the basin. This experiment will give the data off the concentrations and the time.The conclusion of this research is the pressure drop by dry plate can provide the correlation hD = 8.34926( )( ) Lh GgUρρ22. The value of residual pressure drop at the column of sieve plate without baffle and with use abaffle in this study almost constant, i.e. 1-2 mm H2O. The relation among the Peclet number, the F factor andthe flow rate of water can expresse in empirical equation are : for without baffle Pe = 0.3837 F0.9254 Q-0.05229;Baffle V, Pe = 0.00005306 F-2.341 Q-1.005; vertical Baffle Pe = 0.004989 F-1.775 Q-0.4848. The presentation of thedifference of the clear liquid’s height in the condition without use a baffle are 86,88% for the V baffle,53,55% for the vertical baffle (105 l/h); 73,5% for V baffle, 50,64% for the vertical baffle (149 l/h); 84,34 forV baffle, 65,58% for vertical baffle (189 l/h). The value of EMV / EOG for the experiment without use a baffle isgreater than the value of EMV / EOG fot the experiment use a baffle.